SOSIALISASI DAN PELATIHAN TEKNOLOGI IRIGASI HEMAT AIR SERTA BUDIDAYA PADI SISTEM JAJAR LEGOWO 4 : 1 PADA KELOMPOK TANI TARUKO SAIYO - Ramadhan, Nugraha; Dwipa, Indra; Yanti, Nika Rahma; Naspendra, Zuldadan; Hervani, Dini; Muhsanati, Muhsanati; Obel, Obel; Martinsyah, Rachmad Hersi; Sari, Afrima; Utama, Syahrul; Lukito, Chandra; Ronaldi, Ronaldi; Pahlevi, Ilhan; Pasha, Fadhil Kemal (Universitas Mataram, 2024)
In terms of paddy cultivation systems, the Taruko Saiyo farmer group currently still uses a conventional rice cultivation system, both from the irrigation system and the planting method. So there are several problems encountered in this farmer group, namely in the production-management aspect and the socio-cultural aspect. The objectives of the implementation of the Community Partnership Program Helping Nagari Build (PKM-MUB) are: 1) Application of AWD (Alternate Wetting and Drying) technology in order to save the use of irrigation water for Taruko Saiyo farmer groups, 2) Providing assistance for the rice cultivation system of the Jajar Legowo 4: 1 to increase rice production effectively, efficiently and sustainably in the Taruko Saiyo farmer group, and 3) Increasing the level of empowerment of partners from the aspects of production-management and socio-cultural aspects, namely ≥ 75%, and making Taruko Saiyo as an independent farmer group. This community service activity was carried out from July to November 2024. The community service program carried out in the form of socialization, training, and application of technology. In general, partners have understood the technical application of AWD (Alternate Wetting and Drying) technology in order to save the use of rice field irrigation water, as well as the rice cultivation system of the Jajar Legowo 4 method: 1 as an effort to increase rice production effectively, efficiently and sustainably.